3′-Sialyllactose Protects SW1353 Chondrocytic Cells From Interleukin-1β-Induced Oxidative Stress and Inflammation - Baek, Ahreum; Jung, So Hee; Pyo, Soonil; Kim, Soo Yeon; Jo, Seongmoon; Kim, Lila; Lee, Eun Young; Kim, Sung Hoon; Cho, Sung-Rae (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a major degenerative joint disease. Oxidative stress and inflammation play key roles in the pathogenesis of OA. 3′-Sialyllactose (3-SL) is derived from human milk and is known to regulate a variety of biological functions related to immune homeostasis. This study aimed to investigate the therapeutic mechanisms of 3′-SL in interleukin-1β (IL-1β)-treated SW1353 chondrocytic cells. 3′-SL potently suppressed IL-1β-induced oxidative stress by increasing the levels of enzymatic antioxidants. 3′-SL significantly reversed the IL-1β mediated expression levels of reactive oxygen species in IL-1β-stimulated chondrocytic cells. In addition, 3′-SL could reverse the increased levels of inflammatory markers such as nitrite, prostaglandin E2, inducible nitric oxide synthase, cyclooxygenase-2, IL-1β, and IL-6 in IL-1β-stimulated chondrocytic cells. Moreover, 3′-SL significantly inhibited the apoptotic process, as indicated by the downregulation of the pro-apoptotic protein Bax, upregulation of the anti-apoptotic protein Bcl-2 expression, and significant reduction in the number of TUNEL-positive cells in the IL-1β-treated chondrocytic cells. Furthermore, 3′-SL reversed cartilage destruction by decreasing the release of matrix metalloproteinases (MMP), such as MMP1, MMP3, and MMP13. In contrast, 3′-SL significantly increased the expression levels of matrix synthesis proteins, such as collagen II and aggrecan, in IL-1β-treated chondrocytic cells. Furthermore, 3′-SL dramatically suppressed the activation of mitogen-activated protein kinases (MAPK) and phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT)/nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling signaling pathways, which are related to the pathogenesis of OA. Taken together, our data suggest that 3′-SL alleviates IL-1β-induced OA pathogenesis via inhibition of activated MAPK and PI3K/AKT/NF-κB signaling cascades with the downregulation of oxidative stress and inflammation. Therefore, 3′-SL has the potential to be used as a natural compound for OA therapy owing to its ability to activate the antioxidant defense system and suppress inflammatory responses.